Analysis of the Implementation of the Hospital Management Information System (SIMRS) on Waiting Time and Patient Satisfaction - Yani Heryani; Sedarmayanti Sedarmayanti; Etty Sofia Mariaty Asnar; Vip Paramarta; Ayu Laili Rahmiyati; Farida Yuliaty (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Hospital Information Management System (SIMRS) is crucial for speeding up healthcare services and integrating medical data. This study aimed to determine the relationship between SIMRS quality (system quality, information quality, and service quality) and waiting time and patient satisfaction in the outpatient department of RSUD Lembang. This quantitative study employed an analytic cross-sectional design involving 96 outpatients. Data were collected using questionnaires and direct observations of waiting times and were analyzed using Chi-square and Poisson regression analyses. The results showed that most patients experienced waiting times of less than 60 minutes (59.4%) and were satisfied with the hospital services (51.0%), although the information quality and service quality of SIMRS were still rated as poor by most participants. The statistical analyses showed that all dimensions of SIMRS quality were significantly associated with waiting time and patient satisfaction (p < 0.001). Staff service quality in operating the system was the main factor associated with shorter patient waiting times (PR = 2.67). Meanwhile, the technical stability of the computer system was the strongest factor associated with patient satisfaction (PR = 4.90). The study concludes that stable information technology system performance and responsive staff contribute to reducing waiting times and improving patient satisfaction. Hospitals are recommended to integrate computer systems across all service units and provide digital training for staff.